2015
DOI: 10.1007/s13277-014-2752-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of MGMT methylation in colorectal cancer: a meta-analysis and literature review

Abstract: The development of colorectal cancer (CRC) spans about 5-10 years, making early detection and prevention beneficial to the survival of CRC patients. To address inconsistencies in evidence regarding O(6)-methylguanine-DNA-methyltransferase (MGMT) methylation as a potential prognostic factor in CRC, we conducted a meta-analysis to evaluate MGMT methylation in CRC patients. Fourteen studies were included in the meta-analysis after screening 120 articles. The following items were collected from each study: author,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Clinical trials for TMZ in CRC were designed to exploit the association between MGMT deficiency and increased sensitivity to temozolomide [ 41 , 42 ]. Indeed, MGMT promoter hypermethylation and low MGMT expression appear to be early events in CRC patients [ 43 ], consistently with our clinical results. In addition, concomitant downregulation of both MGMT and MPG correlate with an improved response to TMZ [ 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…Clinical trials for TMZ in CRC were designed to exploit the association between MGMT deficiency and increased sensitivity to temozolomide [ 41 , 42 ]. Indeed, MGMT promoter hypermethylation and low MGMT expression appear to be early events in CRC patients [ 43 ], consistently with our clinical results. In addition, concomitant downregulation of both MGMT and MPG correlate with an improved response to TMZ [ 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…We have recently reported that concurrent methylation in NEUROG1 and CDKN2A (p16) is associated with higher recurrence in colorectal cancer patients whereas CIMP classification based on the number of methylated markers was not [ 4 ]. Importance of individual gene methylation such as CHFR , MGMT , and SHISA3 has also been shown in other studies [ 6 , 10 , 11 ].…”
Section: Introductionsupporting
confidence: 64%
“…Remarkably, higher SEPT9 promoter methylation was independently associated with increased DSS in CRC, whereas no prognostic value was depicted for the remainder gene promoters. A meta-analysis that included 14 studies showed that MGMT methylation status was not associated with CRC prognosis [47], whereas RASSF1A promoter methylation has been associated with poor prognosis, although when assessed in plasma samples [30]. Furthermore, CIMP status also did not disclose prognostic value in our study, which is in accordance with a recent metaanalysis that found no significant effect of CIMP status in DFS or OS in 8 out of 11 and in 13 out of 19 studies previously published, respectively [48].…”
Section: Discussionmentioning
confidence: 99%